Effect of the molecular weight and its distribution of polyvinylidene fluoride on the relationship between the spinning process, microstructure and properties of hollow fiber membranes via thermally induced phase separation. Issue 7 (April 2019) - Li, Nana; Chang, Zhe; Lu, Qingchen; Xiao, Changfa; Wu, Junyi; Liang, Congqiang
Polyvinylidene fluoride (PVDF) is an important material in the preparation of ultrafiltration membranes via the thermally induced phase separation (TIPS) method. In this paper, four PVDF hollow fiber membranes with different molecular weights were prepared via the TIPS method by using dibutyl phthalate and dioctyl phthalate as a mixed diluent. The relationship between the molecular weight of PVDF and its distribution, phase separation, crystallization behavior and spinning process has been systematically studied. The effects of three factors on the microstructure and properties of the PVDF membrane have been analyzed. The flow behaviors of the PVDF/diluent and PVDF melt were tested by a capillary rheometer and a melt flow rate instrument, respectively. A phase diagram of the membrane solution was determined by thermal polarizing microscope and differential scanning calorimetry. The crystallization behavior and angle of orientation of the membrane were tested by using a differential scanning calorimeter and a sound velocity orientation measurement instrument. The microstructures, such as the pore structure and crystalline grain structure, were observed by field emission scanning electron microscopy. Meanwhile, the properties of the membrane were examined from the view of water flux, porosity and tensile testing. The results showed that changes in the polymer molecular weights affected not only the dynamics but also the thermodynamics of phase separation in membrane formation. As the PVDF molecular weight increased, the phase separation region increased, but the membrane structure became denser. A wide molecular weight distribution easily produced large pores. Then, the water flux decreased first and then increased.